Trade Liberalization and Performance of the Nigerian Textile Industry - Okeowo, Florence Oluremi; Aregbeshola, Rafiu Adewale (Journal of Economics and Behavioral Studies, 2018)
Nigeria textile industry is characterized by questionable incentives, political uncertainty, acute power shortage, poor infrastructure, smuggling and red-tape bureaucracy, among others. The study modified the endogenous growth model within a time series (1986 and 2015) estimation techniques of Autoregressive Distributed Lagged model (ARDL). Findings revealed that the effect of simple tariff rate on textile industry is negative and statistically significant in the long-run; while trade liberalization policy measure through simple tariff rate has a lag effect before it can be effective in the textile industry. In both short and long run, real effective exchange rate depreciation worsens the performance of the textile industry in Nigeria. In the long run, a 1.0% rise in trade openness would decrease the level of textile industry performance by about 17.49%, while factor affecting textile industry performance in the short run are simple tariff rate, financial development, exchange rate changes, trade openness and labor and capital inputs respectively. The study concluded that Trade liberalization has a lag effect on textile industry performance and a significant effect on the performance of the Nigerian textile industry. It is therefore recommended that government should make concerted efforts toward providing a favorable business environment, reducing inflation and improve the infrastructural facilities for the textile industry to strive.